2019
DOI: 10.1021/acs.bioconjchem.9b00475
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid–Antibody Fragment Bioconjugates for Extended Ocular Pharmacokinetics

Abstract: Treatment of ocular diseases associated with neovascularization currently requires frequent intravitreal injections of antivascular endothelial growth factor (anti-VEGF) therapies. Reducing the required frequency of anti-VEGF injections and associated clinical visits may improve patient adherence to the prescribed treatment regimen and improve outcomes. Herein, we explore conjugation of rabbit and fragment antibodies (Fab) to the biopolymer hyaluronic acid (HA) as a half-life modifying strategy, and assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Most approaches currently pursued for ocular half-life extension aim to reduce the drug’s diffusivity. This may be accomplished by binding to a vitreous matrix constituent, such as hyaluronic acid or collagen [ 19 , 20 ], by designing a bulky format of large hydrodynamic radius [ 14 , 15 , 16 , 17 ] or by enabling it to associate with soluble endogenous macromolecules, such as albumin, and form high MW complexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most approaches currently pursued for ocular half-life extension aim to reduce the drug’s diffusivity. This may be accomplished by binding to a vitreous matrix constituent, such as hyaluronic acid or collagen [ 19 , 20 ], by designing a bulky format of large hydrodynamic radius [ 14 , 15 , 16 , 17 ] or by enabling it to associate with soluble endogenous macromolecules, such as albumin, and form high MW complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A HSA binding immunoglobulin single variable domain (nanobody, VHH) sequence (ALB8 from WO 2012/131078 A1 [ 33 ]) was recombinantly fused via a 3× GGGGS-linker to the C-terminus of the heavy chain of a species-matched rabbit Fab (rabFab) [ 17 ]. The C-terminus of the nanobody was modified by a His6-tag (FabA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a tenfold increase in the drug half-life with no change in pharmacological activity. Famili et al [31] developed hyaluronic acid-fragment antigen-binding (Fab) bioconjugates for anti-VEGF therapies. They found that conjugation of Fab with negatively charged hyaluronic acid significantly slowed in vivo clearance from rabbit vitreous humor after intravitreal injection.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Driven by the technological advances in material science and medical devices, various LA delivery systems have been applied in the treatment and prevention of diseases. 4,5 LA drug products consist of a range of mature and emerging delivery platforms, including polymer based micro-and nano-particulate systems, 5−7 polymeric implants, 8,9 in-situ forming hydrogels, 10−12 polymer-solvent depots, 13 polymer drug conjugates 14 and lipid-based liquid crystals 15,16 for subdermal insertion. Polymer matrices, lipid systems, and matrices formed by self-assembling active pharmaceutical ingredient (API) 17 are also used to achieve extended drug release owning to their unique physical properties.…”
Section: Introductionmentioning
confidence: 99%